(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
Public institutions play a central role in fostering development through their interventions across economic and social sectors, thereby contributing to the implementation of national policies and programs alongside the state. Within this framework, education emerges as the second national priority after territorial integrity, which justifies the ongoing reform process of the system, particularly the Regional Academies of Education and Training (AREF). This article contributes to the scholarly debate on public financial oversight and the activation of mechanisms of good governance in the public sector. It offers an analytical reading of the Moroccan legal texts that frame these institutions and explores reform pathways through a dual methodological approach: a legal-analytical perspective and a systemic perspective aimed at examining institutional interactions.